2017
DOI: 10.1002/adma.201704695
|View full text |Cite
|
Sign up to set email alerts
|

Printing Semiconductor–Insulator Polymer Bilayers for High‐Performance Coplanar Field‐Effect Transistors

Abstract: Source-semiconductor-drain coplanar transistors with an organic semiconductor layer located within the same plane of source/drain electrodes are attractive for next-generation electronics, because they could be used to reduce material consumption, minimize parasitic leakage current, avoid cross-talk among different devices, and simplify the fabrication process of circuits. Here, a one-step, drop-casting-like printing method to realize a coplanar transistor using a model semiconductor/insulator [poly(3-hexylthi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…P‐type OFETs with PS dielectrics exhibiting excellent stability under positive gate‐bias stress have been reported previously, [ 66,67 ] unless an elevated temperature is used to inject electrons into PS layer. [ 36,39,43 ]…”
Section: Resultsmentioning
confidence: 99%
“…P‐type OFETs with PS dielectrics exhibiting excellent stability under positive gate‐bias stress have been reported previously, [ 66,67 ] unless an elevated temperature is used to inject electrons into PS layer. [ 36,39,43 ]…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, appropriate hydroxyl‐free polymers, such as a divinyl‐tetramethylsiloxane‐bis(benzocyclobutene) derivative, can also be used as surface modifiers on SiO 2 dielectrics to achieve better n‐type charge‐transport behaviors in conjugated polymers . In fact, polymer coating has been demonstrated as a powerful method to modify the dielectric surface and improve the performance of OFETs . For example, Kim et al reported that the performance of pentacene FETs with a bottom‐gate top‐contact (BGTC) configuration could be modulated by changing the surface conditions of a polymer dielectric with different molecular structures due to their influence on the grain size/crystallinity of pentacene films.…”
Section: Interface Modification Methodsmentioning
confidence: 99%
“…It is well known that the ability to transport the charge carriers between the electrodes and organic layers is very crucial to obtain highly efficient electronic devices . A mismatch between the energy levels of organic layers and inorganic electrodes leads to the generation of an energy barrier that hampers the extraction or injection of charge carriers .…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Recently, a significant attention has been paid to the use of zwitterions owing to their solubility in polar solvents for solution processing, [15][16][17] and dipole formation for the transfer of carriers [18][19][20] and ions. [24] A mismatch between the energy levels of organic layers and inorganic electrodes leads to the generation of an energy barrier that hampers the extraction or injection of charge carriers. The presence of both negative and positive ions in the same molecule enables zwitterions to develop interfacial dipole.…”
mentioning
confidence: 99%
See 1 more Smart Citation